The South African Parkinson's Disease Study Collection. Issue 1 (22nd October 2021) - van Rensburg, Zuné Jansen; Abrahams, Shameemah; Chetty, Devina; Step, Kathryn; Acker, Debbie; Lombard, Carl J.; Elbaz, Alexis; Carr, Jonathan; Bardien, Soraya
Abstract : Parkinson's disease (PD) incidence is increasing in sub‐Saharan Africa. We recruited 687 individuals with PD from different ancestral groups across South Africa. More Afrikaner Europeans had early‐onset PD than other ancestral groups. More men had PD than women, with a younger age at onset for men (56 years).